Syntheses, crystal structures, Hirshfeld surface analyses and crystal voids of 1-(4-bromophenyl)-2,2-dichloroethan-1-one and 2,2-dibromo-1-(p-tolyl)ethan-1-one - Atash V. Gurbanov; Firudin I. Guseinov; Aida I. Samigullina; Tuncer Hökelek; Khudayar I. Hasanov; Tahir A. Javadzade; Alebel N. Belay (Acta Crystallographica Section E: Crystallographic Communications, 2025)
The asymmetric units of the compounds, C8H5BrCl2O (I), and C9H8Br2O (II), contain two and one crystallographically independent molecules, respectively. In compound (I), the planar rings are oriented at a dihedral angle of 13.23 (8)°. In crystals of both compounds, intermolecular C—H...O hydrogen bonds link the molecules into infinite chains along the b-axis direction. In crystal of (I), there are π–π interactions between the centroids of the parallel rings with centroid-to-centroid distances of 3.5974 (14), 3.6178 (16) and 3.9387 (16) Å while neither π–π nor C—H... π(ring) interactions are present in (II). The Hirshfeld surface analyses of the crystal structures indicate that the most important contributions for the crystal packings are from H...Cl/Cl...H (27.5%), H...O/O...H (15.0%), H...Br/Br...H (10.2%) and H...H (9.0%) for (I) and H...Br/Br...H (36.1%), H...H (22.2%), H...O/O...H (14.1%) and H...C/C...H (13.9%) for (II). Hydrogen bonding and van der Waals interactions are the dominant interactions in the crystal packings. The volumes of the crystal voids and the percentages of free spaces in the unit cells were calculated to 111.55 Å3 and 12.27% for (I) and 63.37 Å and 6.69% for (II), showing that no large cavities are present in either structure.